Pelatihan dan Pendampingan Penggunaan CMS Aplikasi Desa Online Bagi Desa-Desa di Kabupaten Kebumen - Siti Khomsah; Ummi Athiyah; Aditya Dwi Putro Wicaksono; Novanda Alim Setya Nugraha (LPPM IT Telkom Purwokerto, 2023)
Nowdays, about 60 villages in Kebumen Regency have website, this practiacally as village information system. The application was made local government, the agency of Kebumen Communication and Information Service (Diskominfo). Villages are provided with facilities by Kominfo, they are domain andserver. Meanwhile, the Village is obliged to manage as the Content Management System (CMS) admin. However, many villages has problems in managing the CMS , such as capability of village’s staff to operate CMS. Thus, many online village websites do not update data continuously and are even not used optimally. Therefore, this community service aims to increase the capacity of village staff in Kebumen Regency to managing online village CMS. This service uses training and mentoring methods. Target of this services are 60 villages but only 41 villages participate in this activities. The results of survey showed this community service increase knowledge and skills participant for managing their website. The impact on knowledge and skills reaches more than 3 and the value of a good response is 3.38 on a scale of 1-4. The continuity of content updates is also an indication that this training has an impact on improving the management of online village websites.